Utilizing Local Cocoa as Ready to Drink Beverage with Various Flavors and Supporting Cocoa Farmers Empowerment in Samarinda - Andi Rachmat Aidil Alfadlan; Vera Anita; Marsha Anindita (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Cokelat Harapan was established as a solution to increase cocoa consumption and empower cocoa farmers in Indonesia, particularly in Samarinda and Blitar. The enterprise focuses on developing ready-to-drink chocolate beverages in various flavors, utilizing local cocoa to support the local economy. Through collaborations with farmers and chocolate production companies, Cokelat Harapan aims to become a chocolate retail company with a focus on research and development. Its primary mission is to empower cocoa farmers by providing them with a share of the profit not only from cocoa purchases but also from the utilization of cocoa sold back to the market.